Factors Related to Stress Levels in School-Age Children in South Tangerang City Elementary School in 2024 - Vivi Silawati; Nabilah; Suprihatin (International Health Sciences Journal, 2024)
According to WHO (World Health Organization), stress is the fourth health problem in the world and will be number two in 2020, the prevalence of stress is quite high, namely 350 million people in the world experience stress. The prevalence of student stress in the world is 38.91%, in Asia 61.3% and Indonesia 71.6%. The purpose of this research was to determine the factors related to stress levels in school-age children at SDN Kota Tangerang Selatan in 2024. Analytical survey research with a cross-sectional approach. The sample in this study were students at SDN Kota Tangerang Selatan as many as 90 students in grade 6 and were taken using the total sampling technique. Data were obtained by distributing questionnaires. Data analysis was carried out univariately and bivariately with the Spearman test. The study results showed that out of 90 respondents, 25 people (27.8%) had severe stress. There was a relationship between parenting patterns and stress levels in school-age children (P = 0.018) with a low correlation strength (Zcount = 0.249), there was a relationship between class conditions and stress levels (P = 0.001) with a low correlation strength (Zcount = 0.354), there was a relationship between tasks and stress levels (P = 0.004) with a low correlation strength (Zcount = 0.304), there was a relationship between school exams and stress levels (P = 0.039) with a low correlation strength (Zcount = 0.218), there was a relationship between personality and stress levels (P = 0.012) with a low correlation strength (Zcount = 0.262), and there was a relationship between gender and stress levels in school-age children (P = 0.000) with a moderate correlation strength (Zcount = 0.591). These findings indicate that student stress was influenced by various environmental and individual factors. Schools and parents should pay attention to these factors and create an environment that supports children's mental development. Special assistance during exams, workload management, and good parenting can reduce students' stress levels.